The effectiveness of celebrity endorsement in aspiring new celebrities: Examining the effects of brand, congruence, charisma and overexposure. Issue 3 (9th July 2018) - Freire, Otávio; Quevedo-Silva, Filipe; Senise, Diego; Scrivano, Pedro
Abstract : Purpose: Celebrity endorsement is a phenomenon widely used by companies and studied by researchers. Despite the generally positive aspects of endorsement on the evaluation of products, in some cases, celebrities cannot substantially help promote products. The purpose of this paper is to analyze the effectiveness of celebrity endorsement effect in an aspiring new celebrity. Design/methodology/approach: Four studies involving 664 respondents were conducted to analyze the effectiveness of the endorsement. In addition to verifying the existence of the effect (Study 1), studies were conducted focusing on contextual variables with the potential to modify effect. Study 2 analyzes the brand and charisma effects, Study 3 analyzes the congruence between celebrities and Study 4 analyzes the exposure level of the endorser celebrity. Findings: The results demonstrate the effectiveness of this celebrity endorsement, as well as the effect of different contexts on endorsement, demonstrating that although new celebrities are less affected by acclaimed celebrities, as they become better known, to use the endorsement of celebrities with charisma and who relating in some way to the aspiring celebrity, can be an effective strategy, especially for the beginners in the career. Originality/value: This research contributes to the knowledge of celebrity endorsement to fill the lack pointed out in previous studies in the field over the effectiveness of this effect and, above all, the moderator variables that can influence or even annul this effect. In addition, by developing its own image and reputation, the aspiring new celebrity receives less influence from the endorser.